2015
DOI: 10.1038/srep11516
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the long non-coding RNA H19 in plasma as a novel biomarker for diagnosis of gastric cancer

Abstract: Recent studies have demonstrated that long non-coding RNAs (lncRNAs) are regarded as useful tools for cancer detection, particularly for the early stage; however, little is known about their diagnostic impact on gastric cancer (GC). We hypothesized that GC-related lncRNAs might release into the circulation during tumor initiation and could be utilized to detect and monitor GC. 8 lncRNAs which previously found to be differently expressed in GC were selected as candidate targets for subsequent circulating lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
250
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(257 citation statements)
references
References 28 publications
(29 reference statements)
5
250
2
Order By: Relevance
“…Furthermore, increased expression of H19 was markedly associated with an early recurrence of bladder cancer and may be considered a predictive marker for poor prognosis (14). Zhou et al (21) revealed that plasma H19 expression enabled the differentiation of early stage gastric cancer from controls with an area under the curve of 0.877, sensitivity of 85.5% and specificity of 80.1% (18).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased expression of H19 was markedly associated with an early recurrence of bladder cancer and may be considered a predictive marker for poor prognosis (14). Zhou et al (21) revealed that plasma H19 expression enabled the differentiation of early stage gastric cancer from controls with an area under the curve of 0.877, sensitivity of 85.5% and specificity of 80.1% (18).…”
Section: Discussionmentioning
confidence: 99%
“…Given that EVs have been detected in many different body fluids, circulating H19 could serve as a biomarker for non-invasive cervical cancer screening, akin to the use of plasma H19 in gastric cancer diagnosis. 41 A growing number of reports have explored the effect of H19 loss-and gain-of-function in various malignancies. 27,[42][43][44] However, data on the role of H19 in cervical cancer remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MALAT-1-derived miniRNA can be used as a novel plasma-based biomarker for PCa detection and can improve diagnostic accuracy by predicting prostate biopsy outcomes. Later, Zhou et al reported the potential diagnostic value of plasma lncRNA H19 in gastric cancer [5]. In addition, in the field of esophageal squamous cell carcinoma diagnosis, plasma lncRNA POU3F3 was able to serve as a potential biomarker [12].…”
mentioning
confidence: 99%
“…The quantity of circulating RNAs is also dependent on its degradation and clearance rate. Circulating noncoding RNAs (ncRNAs) have also been thought to be derived from peripheral blood cells [6], although other studies have not found a significant association between plasma long ncRNA (lncRNA) concentrations and peripheral hematocytes [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation